New insights into structural organization and gene duplication in a 1.75‐Mb genomic region harboring the α‐gliadin gene family in Aegilops tauschii, the source of wheat D genome. (9th October 2017) - Huo, Naxin; Dong, Lingli; Zhang, Shengli; Wang, Yi; Zhu, Tingting; Mohr, Toni; Altenbach, Susan; Liu, Zhiyong; Dvorak, Jan; Anderson, Olin D.; Luo, Ming‐Cheng; Wang, Daowen; et al.
Summary: Among the wheat prolamins important for its end‐use traits, α‐gliadins are the most abundant, and are also a major cause of food‐related allergies and intolerances. Previous studies of various wheat species estimated that between 25 and 150 α‐gliadin genes reside in the Gli‐2 locus regions. To better understand the evolution of this complex gene family, the DNA sequence of a 1.75‐Mb genomic region spanning the Gli‐2 locus was analyzed in the diploid grass, Aegilops tauschii, the ancestral source of D genome in hexaploid bread wheat. Comparison with orthologous regions from rice, sorghum, and Brachypodium revealed rapid and dynamic changes only occurring to the Ae. tauschii Gli‐2 region, including insertions of high numbers of non‐syntenic genes and a high rate of tandem gene duplications, the latter of which have given rise to 12 copies of α‐gliadin genes clustered within a 550‐kb region. Among them, five copies have undergone pseudogenization by various mutation events. Insights into the evolutionary relationship of the duplicated α‐gliadin genes were obtained from their genomic organization, transcription patterns, transposable element insertions and phylogenetic analyses. An ancestral glutamate‐like receptor ( GLR ) gene encoding putative amino acid sensor in all four grass species has duplicated only in Ae. tauschii and generated three more copies that are interspersed with the α‐gliadin genes. Phylogenetic inference and different gene expression patterns support functional divergence of the Ae. tauschii GLR copies after duplication. Our results suggest that the duplicates of α‐gliadin and GLR genes have likely taken different evolutionary paths; conservation for the former and neofunctionalization for the latter. Significance Statement: The α‐gliadins are important for wheat grain quality, but the complex Gli‐2 loci encoding them are still poorly resolved. We report the complete sequence and gene expression patterns of the Gli‐2 locus of A. tauschii, the progenitor of wheat D genome. Dynamic structural and evolutionary changes (e.g., frequent insertion of non‐syntentic genes and recurrent tandem gene duplication) were revealed for Gli‐2, thus facilitating further basic and applied research on prolamins in wheat and related species.